Youth and Adults in the Prison System: research notes on the Brazilian experience - Julião, Elionaldo Fernandes (Education Policy Analysis Archives, 2013)
Education for youth and adults in situations of restriction and deprivation of freedom in Brazil over the last few years, has been consolidated as a national public policy. Among the main achievements include the adoption of national guidelines that regulate political principles underlying referrals and educational for its implementation in the states. Contributing to discussions implemented, especially in academic areas, this article results from research conducted over 15 years of study, aims to present some reflections on the school in the Brazilian prison system and the role of education for youth and adults context of deprivation of liberty. Among the main arguments stand out, in general terms, the everyday school spaces in the prison, the profile of professionals working in these schools, the student profile, internal prison; questions about reading and the existence of libraries in the prison, and on methodological perspectives implemented in schools in the penitentiary system.